Autobiographical Statements in Twentieth-Century Russian Literature - Harris, Jane Gary (Book collections on Project MUSE., 2014)
The fifteen essays in this volume explore the extraordinary range and diversity of the autobiographical mode in twentieth-century Russian literature from various critical perspectives. They will whet the appetite of readers interested in penetrating beyond the canonical texts of Russian literature. The introduction focuses on the central issues and key problems of current autobiographical theory and practice in both the West and in the Soviet Union, while each essay treats an aspect of auto-biographical praxis in the context of an individual author's work and often in dialogue with another.